(3GOGQI GdeNRhf GdSdYj (B/s - (3GdUjQaj, eMeOs; (3GdYdGb, HTjQ YHGS s ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2002)
(3eaghe GdeNRhf hCfhGYg(B- (3JMdjd GdeNRhf(B- (3JcGdja GdeNRf (B((3JcGdja, GdJNWjW, GdeQGbHI (B) - (3GdOaYI GdEbJUGOjI ddeNRhf(B- (3JhUja hJHhjH hJQejR GdeNRhf(B- (3JNWjW GdeNRhf(B- (3eQGbHI GdeNRhf(B- (3GdeYGdLI GdeMGSHjI dLQO GdeNRhf(B- (3eTcdGJ GdeNRhfs
Keywords: (3GdGOGQIs; (3GdSdYs; (3GdeNGRfs